A broadband cooperative relay-based system for power line communication - Aiyelabowo, O. P. (2018)
Demand for data for various broadband applications has placed the power line communication (PLC) in a prime place. In PLC, the existing electrical power installation in the last mile is used as the transmission medium, hence no new installation is required. Since transmission of broadband data was not intended over the electrical power installation, the network (power line) poses a great deal of impediment to broadband data as it traverses the medium. These impediments are, attenuation over the length of the cable, noise (impulsive and Gaussian), and multipath fading. Hence, signals propagation over the line is either received corrupted at the destination or lost out rightly. This work implements a technique to maximize channel capacity, reduce attenuation characteristic, symbol error rate and outage probability in the PLC. Performance of the system is compared with those of MIMO-PLC and PLC-repeaters (PLC-rep.). In the first instance, the attenuation over the long length of the power line network was combatted. A customized cooperative relaying system, implementing amplify-and-forward (AF) and decode-and-forward (DF), with placement of the relay modem at three different locations along the network in the PLC was developed. A noise mitigation system was incorporated to improve the system’s bit error rate (BER). The systems’ performance for channel capacity improvement between 18.32% and 73.5% and 144% and 260% over the MIMO-PLC and PLC-rep. was achieved for AF and DF schemes respectively. SER reduction on the PLCC AF and DF are 43.41% and 85.16% over the MIMO-PLC and 69.26% and 91.9% over the PLC-rep., while outage probability reduced by 96.2% and 99%. Attenuation reduction to 31.4% was achieved with the DF link when the relay was placed 10 m away from source node. To achieve performance maximization inspite the branches on the network, PLCC multiple relaying scheme, having three different multiple relay scenarios was arrayed. Selective relaying, implementing best relay channel instantaneous SNR, was deployed for AF and DF, hence, best relay is selected. Selective relaying improved the system’s channel capacity by 201%, 303% and 70.6% over MIMO-PLC, PLC-rep. and PLCC (fixed) respectively. Owing to the noise mitigation system, the SER reduced 400% over the duo of MIMO-PLC and PLC-rep. and by 79.37% over the PLCC (fixed) schemes. Outage probability achieved a land marking drop over the benchmark links and 87.5% over the PLCC (fixed) link. Further reduction in attenuation was achieved to 64.1% with the 7 relay DF deployment. Finally, to keep the system’s maximized performance within the electromagnetic compatibility framework, optimal power ratio was developed for optimal power allocation between source and relay modems. Objective function for maximizing and minimizing the direct and cooperative transmission power was developed for optimal power ratio. The optimal power allocation (OPA) algorithm allocates one-third and two-third of the transmitted power (Pt) to the source and relay modems, direct and cooperative transmissions respectively. Channel capacity improved by 274% and 44.37% over the MIMO-PLC and equal power allocation (EPA) scheme and achieved 457% improvement over the PLC-rep. SER with OPA reduced drastically over the benchmark links and 76.1% over the EPA scheme, while outage probability further reduces with OPA largely over the benchmark links and 90% over the EPA. The attenuation reduction is also prominent with the OPA scheme. The abstract is a digest of the entire thesis and should be given the same consideration as the main text. It does not normally include any reference to the literature. Abbreviations or acronyms must be preceded by the full term at the first use.